A Study of Learning Management Using Flipped Classroom Approach with Cooperative Learning Together Technique on MswLoGo Program Unit of 9th Graders - สาระมู วิไลวรรณ; จงกลกลาง สิรินาถ (Ratchaphruek Journal, 2018)
ABSTRACT This research aimed to 1) study group working, responsibility skills and learning achievement, 2) compare group working, responsibility skills,3) learning achievement between before and after implementation and compare learning achievement after implementation was higher than the criteria of 70% ,and 4) evaluate students’ task using flipped classroom approach with cooperative learning together technique on MswLogo program for 9thgraders. The samples were 39 students in 9th grade of Bunlua Wittayanusorn School in the second semester of academic year 2016. The research instrument were 6 lesson plans for 12 hours. The evaluation of group working and responsibility skills, learning achievement test and job evaluation was implemented and analyzed by percentage, average, Standard Deviation and t-score. The results declared the conducted flipped classroom approach with cooperative learning together technique as: 1) The responsibility skills had the highest score, 2) The group working skills had high score with progress as 2.16 (43.28%), 3) The posttest was higher than pretest of the level of significance .05., 4) The learning achievement of students had score average as 16.10 (53.68%) the posttest was higher than pretest as 70% in level of significance .05.